A numerical comparative study of completion methods for pairwise comparison matrices - Hailemariam Abebe Tekile; Matteo Brunelli; Michele Fedrizzi (Operations Research Perspectives, 2023)
In the context of some multi-criteria decision-making methods, such as the Analytic Hierarchy Process, an expert is required to compare entities, e.g. alternatives and criteria. However, often, for various reasons, the expert cannot provide judgments on all pairs of entities. For these cases, several completion methods have been proposed in the literature to estimate the missing values of pairwise comparison matrices. In this paper, we study the similarity of eleven completion methods on the basis of numerical simulations and hierarchical clustering. We perform simulations for matrices of different orders considering various numbers of missing comparisons. Finally, the results suggest the existence of a cluster of five extremely similar methods, and a method significantly dissimilar from all the others.
Keywords: 650; Consistency; Analytic hierarchy process; Hierarchical clustering; Incomplete pairwise comparison matrix; Pairwise comparison matrix